General-practitioner Hospital Beds: A Review. Issue 5746 (20th February 1971) - Israel, S.; Draper, P.
Abstract : This paper reviews literature related to general-practitioner hospital beds. In England and Wales 21% of all maternity beds are controlled by general practitioners rather than consultants, and the proportion has increased considerably since 1955. Nearly one in five of these 21% are sited in the wards of a consultant hospital. General-practitioner beds, other than maternity, represent 3% of all hospital beds (excluding psychiatric beds) and this proportion has remained constant over the past 15 years. Only about 1% of these general-practitioner beds are located in a consultant hospital. In the discussion three questions are raised: Will general-practitioner inpatient care have a useful function in the future? What might that function be? Where should the care be located? The broader issue of the future role of the general practitioner needs to be considered before these questions can be satisfactorily answered. Unless a "hospital orientated" role of the general practitioner prevails there seems little place for practitioner inpatient care in urban areas. In the more rural areas, however, whatever the role of the practitioner becomes, certain groups of patients might advantageously receive inpatient care from their practitioners. Firmer answers to the questions raised cannot be given until a co-ordinated programme of research and development concerning different patterns of care is started.